Den estniska dialektordboken i relation till andra jämförbara verk - Haak, Anu (Nordiske Studier i Leksikografi, 1997)
Fascicle 1 ofthe Estonian Dialect Dictionary was published in 1994. By now 5 fascicles (1300 pp. in all) have been published. Volume 1 of the Finnish Dialect Dictionary saw light in 1985. By now 5 volumes have come out (4632 pp. in all). Ofthe Swedish Dialect dictionary 2 fasciles have been published, Fasc. 1 (80 pp.) in 1991 and Fasc. 2 (79 pp.) in 1994. All three are big dictionaries designed to comprise the whole vocabulary of all dialects ofthe respective languages. The collection of the material for those dictionaries has been a matter of decades, involving hundreds of contributors. The compilation of the manuscript has been a longlasting process too, during which the principles ofmaterial presentation have undergone some rather radical changes. With the recent arrival of the publication stage the editors had to take the: final decision about the format ofthe dictionary, so as to provide the future user with maximum information on eveiy dialect of the language. This was certainly not an easy task to cope with as the publication of the final volumes was (and still is) far ahead, with some unforeseeable problems bound to crop up, but the decisions not to be reconsidered any more. The following is an attempt to find out how the different dictionaries have set about the challenge ofmatching ideals with reality.